2011
DOI: 10.1007/s10584-011-0025-9
|View full text |Cite
|
Sign up to set email alerts
|

Expected changes in agroclimatic conditions in Central Europe

Abstract: During the past few decades, the basic assumption of agroclimatic zoning, i.e., that agroclimatic conditions remain relatively stable, has been shattered by ongoing climate change. The first aim of this study was to develop a tool that would allow for effective analysis of various agroclimatic indicators and their dynamics under climate change conditions for a particular region. The results of this effort were summarized in the AgriClim software package, which provides users with a wide range of parameters ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 38 publications
(39 reference statements)
4
49
0
3
Order By: Relevance
“…Trnka et al (2011) reported that 98% of agricultural land within a Central European region could shift towards a new agro-climatic class by 2050 -assuming worst case scenario from a down-scaled global climate change model.…”
Section: Regionmentioning
confidence: 99%
“…Trnka et al (2011) reported that 98% of agricultural land within a Central European region could shift towards a new agro-climatic class by 2050 -assuming worst case scenario from a down-scaled global climate change model.…”
Section: Regionmentioning
confidence: 99%
“…Band 2, Kapitel 3), mit einer Zunahme des Bewässerungsbedarfes zur Erhaltung des heutigen Ertragsniveaus (Ertragssicherung) zu rechnen ist (vgl. Band 2, Kapitel 2, Kromp-Kolb et al, 2007;Thaler et al, 2012;Trnka et al, 2011;WPDA, 2011). Die Zunahmen im relativen Wasserbedarf für die Hauptackerbaugebiete im Osten Österreichs liegen unter diesen Klimaverände-rungen für Getreide im Mittel bei ca.…”
Section: Anpassungen In Der Landwirtschaftlichen Bewäs-serungunclassified
“…The changes in agroclimatic conditions in Central Europe are expected to go along with an increase in air temperature, changes in the amount and distribution of precipitation, and prolonged growing seasons. This may lead to a lower productivity of rainfed spring crops due to a higher risk of drought (Trnka et al, 2011). Promising opportunities may arise under these conditions for adopting crops with a pronounced warm-season growth habit such as chickpea (Cicer arietinum L.) in comparatively cool, northern latitude areas (Gan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%